Cutting Edge objects and the art of data modeling. - Esposito, Dino.
Dino Esposito discusses strategies to handle situations where multiple models help you develop more layered and robust applications.
Keywords: ActiveX; Data access layer; Object-relational mapper (ORM).; ADO.NET.